High anti-viral protection without immune upregulation after interspecies Wolbachia transfer. - Ewa Chrostek (PLoS ONE, 2014)
Wolbachia, endosymbionts that reside naturally in up to 40-70% of all insect species, are some of the most prevalent intracellular bacteria. Both Wolbachia wAu, naturally associated with Drosophila simulans, and wMel, native to Drosophila melanogaster, have been previously described to protect their hosts against viral infections. wMel transferred to D. simulans was also shown to have a strong antiviral effect. Here we directly compare one of the most protective wMel variants and wAu in D. melanogaster in the same host genetic background. We conclude that wAu protects better against viral infections, it grows exponentially and significantly shortens the lifespan of D. melanogaster. However, there is no difference between wMel and wAu in the expression of selected antimicrobial peptides. Therefore, neither the difference in anti-viral effect nor the life-shortening could be attributed to the immune stimulation by exogenous Wolbachia. Overall, we prove that stable transinfection with a highly protective Wolbachia is not necessarily associated with general immune activation.